Short-term costs and cost-efficiency of HPV triage strategies in a high HIV-prevalence setting: Evidence from Botswana - Adriane Wynn; Devon Harris; Anna Modest; Maria de Fatima Reyes; Bridgette Wamakima; Kelebogile Gaborone; Natasha Moraka; Annika Gompers; Sikhulile Moyo; Roger Shapiro; Doreen Ramogola-Masire; Rebecca Luckett (PLoS ONE, 2025)
Cervical cancer remains the leading cause of cancer death among women in sub-Saharan Africa and is more severe in high HIV-burdened countries due to persistent high-risk human papillomavirus (hrHPV). In 2021, the World Health Organization recommended primary hrHPV testing for cervical cancer screening; however, optimal triage strategies following positive hrHPV tests remain unclear. We conducted a prospective cost analysis of triage methods for positive hrHPV results among women living with and without HIV in Gaborone, Botswana. We used a micro-costing approach from the perspective of the healthcare provider. The main outcomes were the implementation costs associated with three triage strategies following hrHPV testing: 8-type HPV genotype restriction, visual inspection with acetic acid (VIA), and colposcopy. We also compared the strategies by measuring the change in costs divided by the change in number of true cases of cervical intraepithelial neoplasia (CIN) 2 or worse (CIN2+) identified, based on the results of a prospective cohort study. Results indicated that the 8-type HPV genotype restriction strategy was the most cost-efficient, requiring no additional costs beyond hrHPV testing and identifying the highest number of true CIN2 + cases. VIA and colposcopy triage identified fewer true cases of CIN2+ and incurred additional costs, with colposcopy being the most expensive. Results were consistent in women with and without HIV. Sensitivity analysis highlighted personnel and hrHPV test kit cartridge costs as significant drivers of overall costs. Post-hoc analysis incorporating average treatment costs for precancer demonstrated that genotyping remained dominant at lower treatment costs but became less favorable as treatment costs increased. We found that 8-type genotype restriction was optimal compared to hrHPV screening combined with VIA or colposcopy. Cost estimates can inform future studies that examine the long-term costs and health outcomes of HPV-based two-stage screening algorithms.